Gambaran status karies dan status gizi pada murid TK Kartika XX-16 Manado - Rengkuan, Raissa Y.E.; Wowor, Pemsi M.; Mintjelungan, Christy N. (e-GiGi, 2017)
Abstract: Dental caries is a dental hard tissue disease with multifactorial causes. Consumption of food and beverages improperly and less of dental treatment affect dental caries status and nutritional status. This study was aimed to obtain the profile of dental caries status and nutritional status of kindergarten students of Kartika XX-16 Manado. This was a descriptive study with a cross sectional design. Subjects were selected using nonprobability sampling method with consecutive sampling technique. There were 71 students as the total population; 48 students were selected as subjects. Deciduous dental examination was performed to assess the dental caries status using the dmf-t index. Body weight, height, and age were noted to assess the nutritional status using antrophometric indices based on z score to obtain the body mass index for age (BMI for age). The results showed that the dental caries status of the subjects was at high category (dmf-t index of 4.92). There were 37 subjects (77.1%) who had caries experience in primary teeth and 11 subjects (22.9%) with caries-free primary teeth. Of all subjects, 93.75% had normal nutrition status and 6.3% had nutritional problems. Conclusion: In general, the kindergarten students of Kartika XX–16 Manado had dental caries status of high category, however, their nutritional status was quite good.Keywords: dental caries status, nutritional status Abstrak: Karies gigi merupakan suatu penyakit jaringan keras gigi dengan penyebab multifaktorial. Konsumsi makanan dan minuman dengan pola yang tidak tepat, serta kurangnya pemeliharaan kesehatan gigi berdampak pada status gizi dan status karies gigi anak. Penelitian ini bertujuan untuk mengetahui gambaran status karies gigi dan status gizi pada murid TK Kartika XX-16 Manado. Jenis penelitian ialah deskriptif observasional dengan desain potong lintang. Jumlah populasi 70 orang murid dengan subyek 48 anak diperoleh menggunakan metode nonprobability sampling dengan teknik consecutive sampling. Pemeriksaan gigi-geligi sulung untuk menilai status karies gigi. Penilaian status karies gigi menggunakan indeks dmft. Pemeriksaan berat badan, tinggi badan, dan usia untuk menilai status gizi. Penilaian status gizi menggunakan indeks antropometri berdasarkan z-skor terhadap indikator indeks massa tubuh menurut umur (IMT/U). Status karies gigi murid TK Kartika XX–16 Manado berada pada kategori tinggi dengan indeks dmf-t 4,92. Jumlah subyek dengan riwayat karies gigi sulung sebanyak 37 anak (77,1%) sedangkan yang bebas karies gigi sulung sebanyak 11 anak (22,9%). Status gizi murid TK Kartika XX–16 Manado terdiri dari 93,75% status gizi normal dan 6,3% bermasalah gizi. Simpulan: Murid TK Kartika XX–16 Manado umumnya mempunyai status karies gigi pada kategori tinggi sedangkan status gizi cukup baik.Kata kunci: status karies gigi, status gizi